RELEVANSI NILAI SILA KEEMPAT PANCASILA DALAM TANGGAPAN DIGITAL TERHADAP ISU PERJOKIAN UJIAN TOEFL DI UNIVERSITAS JEMBER - Balqis, Zarifah Bissaroh; Ratna Endang Widuatie; Bagus Novyanto; M.Daffa Arief Bimasakti; Fina Istaufani; Dina Parianti (JOURNAL SAINS STUDENT RESEARCH, 2025)
Advances in information and communication technology have changed the patterns of social participation among communities, including the academic community in higher education institutions. One recent phenomenon is the October 2025 post by the official @unejtoday account about a case of cheating on the TOEFL Computer-Based English (CBE) exam by active students and alumni of the University of Jember. This study aims to analyze how the values of the Fourth Principle of Pancasila, namely “Democracy guided by the wisdom of deliberation/representation,” are reflected in the digital responses of the campus community to this academic violation. The research method used is descriptive qualitative with digital content analysis of the comments on the Instagram post. Data were collected through digital observation and documentation of public responses, which were then categorized based on the values of deliberation, wisdom, and social responsibility. The results of the study show that the majority of netizens demonstrate moral awareness that reflects the values of democracy and wisdom. However, there are a small number of responses that are still sarcastic and emotional. This study emphasizes the importance of strengthening character education and digital ethics based on Pancasila for students, so that social media can become a forum for wise and constructive deliberation.